Study of correlation between breast feeding and wheezing in children - Potharajula, Sagar; Kadke, Shreedhara Avabratha (International Journal of Contemporary Pediatrics, 2018)
Background: Wheezing is the most common chronic health problem in childhood. Many studies have found protective effect of breastfeeding on wheezing, while few others have not. Hence this study was taken up to find out the correlation between breastfeeding and wheezing in children. Methods: Case control study done in a Medical College Hospital. Cases were children of 2-5yrs age with history of wheezing or who had received nebulisation. Controls were children without history of wheezing or nebulisation. Mothers were interviewed with a predesigned proforma. Results were analysed by Chi square test and Odd’s ratio and p value <0.05 was considered significant. Results: There were 92 cases and 184 controls. Sixteen (53.4%), 48 and 27 cases were breastfed less than 1year, till 2yrs and beyond 2yrs respectively. 14 (46.6%), 128, and 40 were the numbers in control group. Breast feeding duration till 1 year of age is statistically correlated with wheezing with p value of 0.02, higher proportion of children who were breastfed for less than 1 year had wheezing when compared to controls. 26 cases out of 69 were not exclusively breast fed till 6 months and 66 cases out of 207 were exclusively breastfed. Higher proportion of cases who were not exclusively breastfed had developed wheeze although it was not significant statistically. 45 cases (36.8%) were initiated on cow’s milk before 1yr of age, 47 cases (30.5%) were initiated after 1year. Higher proportion of children who were initiated on cow’s milk early had developed wheeze but was not significant statistically. 34 cases and 24 controls had family history of asthma. With family history wheezing episodes were 3.72 times more likely irrespective of breast-feeding duration. Conclusions: Breast feeding gives protection against wheezing in children. Mothers should be encouraged to breast feed their children.